2011
DOI: 10.1021/ci200028n
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Cytochrome P450 Inhibitors and Noninhibitors Using Combined Classifiers

Abstract: Adverse side effects of drug-drug interactions induced by human cytochrome P450 (CYP) inhibition is an important consideration, especially, during the research phase of drug discovery. It is highly desirable to develop computational models that can predict the inhibitive effect of a compound against a specific CYP isoform. In this study, inhibitor predicting models were developed for five major CYP isoforms, namely 1A2, 2C9, 2C19, 2D6, and 3A4, using a combined classifier algorithm on a large data set containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 169 publications
(178 citation statements)
references
References 49 publications
5
172
0
1
Order By: Relevance
“…P450s were already the subject of many QSAR studies (Ekins et al, 1999;Lewis et al, 2001;Riley et al, 2001;Wanchana et al, 2003;Hansch et al, 2004;Mao et al, 2006;Gleeson et al, 2007;Yamashita et al, 2008Yamashita et al, , 2011 as well as inhibitor/noninhibitor classification studies (Jensen et al, 2007;Choi et al, 2009;Cheng et al, 2011). For large ADME/Tox characterization panels, it has been repeatedly found that molecular size plays a major, defining role.…”
Section: Resultsmentioning
confidence: 99%
“…P450s were already the subject of many QSAR studies (Ekins et al, 1999;Lewis et al, 2001;Riley et al, 2001;Wanchana et al, 2003;Hansch et al, 2004;Mao et al, 2006;Gleeson et al, 2007;Yamashita et al, 2008Yamashita et al, , 2011 as well as inhibitor/noninhibitor classification studies (Jensen et al, 2007;Choi et al, 2009;Cheng et al, 2011). For large ADME/Tox characterization panels, it has been repeatedly found that molecular size plays a major, defining role.…”
Section: Resultsmentioning
confidence: 99%
“…predicting ADME regulatory properties ML classification methods have also been extensively used for predicting regulators of drug ADME properties, particularly the inhibitors of drug efflux and influx transporters for regulating multi-drug resistance ( [13,15,16], improvement of predictive performance by such strategies as the use of expanded training datasets [8,[64][65][66][67], and both objectives [13,16]. The SEs, SPs, and ACs in predicting P-glycoprotein inhibitors are in ranges of 58%-99%, 47%-91%, and 62%-94% respectively.…”
Section: The Exploration Of Machine Learning Classification Methods Formentioning
confidence: 99%
“…The combined classifier approach, illustrated in Figure 9, explores the collective predictive power of multiple ML classifiers, with the probability output of each independent ML model processed by a decision network [13]. This decision network consists of two layers of units, an input layer and an output layer.…”
Section: Combined Classifiers Approachmentioning
confidence: 99%
See 2 more Smart Citations